Concise Review: Patency of Small‐Diameter Tissue‐Engineered Vascular Grafts: A Meta‐Analysis of Preclinical Trials. (28th March 2019) - Skovrind, Ida; Harvald, Eva Bang; Juul Belling, Helene; Jørgensen, Christian Damsgaard; Lindholt, Jes Sanddal; Andersen, Ditte Caroline
Abstract: Several patient groups undergoing small‐diameter (<6 mm) vessel bypass surgery have limited autologous vessels for use as grafts. Tissue‐engineered vascular grafts (TEVG) have been suggested as an alternative, but the ideal TEVG remains to be generated, and a systematic overview and meta‐analysis of clinically relevant studies is lacking. We systematically searched PubMed and Embase databases for (pre)clinical trials and identified three clinical and 68 preclinical trials ([>rabbit]; 873 TEVGs) meeting the inclusion criteria. Preclinical trials represented low to medium risk of bias, and binary logistic regression revealed that patency was significantly affected by recellularization, TEVG length, TEVG diameter, surface modification, and preconditioning. In contrast, scaffold types were less important. The patency was 63.5%, 89%, and 100% for TEVGs with a median diameter of 3 mm, 4 mm, and 5 mm, respectively. In the group of recellularized TEVGs, patency was not improved by using smooth muscle cells in addition to endothelial cells nor affected by the endothelial origin, but seems to benefit from a long‐term (46–240 hours) recellularization time. Finally, data showed that median TEVG length (5 cm) and median follow‐up (56 days) used in preclinical settings are relatively inadequate for direct clinical translation. In conclusion, our data imply that future studies should consider a TEVG design that at least includes endothelial recellularization and bioreactor preconditioning, and we suggest that more standard guidelines for testing and reporting TEVGs in large animals should be considered to enable interstudy comparisons and favor a robust and reproducible outcome as well as clinical translation. Abstract : Systematic meta‐analysis of large animal studies testing patency of tissue‐engineered vascular grafts show that tissue‐engineered vascular graft surface modification, preconditioning, and recellularization increase patency, whereas an increasing graft length and a decreasing diameter decrease patency. Importantly, the scaffold type, endothelial origin, and the addition of smooth muscle cells do not have an immediate effect on tissue‐engineered vascular graft patency.